Epidemiological features of gastroenteropancreatic neuroendocrine tumors in Chengdu city with a population of 14 million based on data from a single institution. Issue 3 (12th May 2016) - Guo, Lin‐Jie; Wang, Chun‐Hui; Tang, Cheng‐Wei
Abstract: Aim: Recent studies on gastroenteropancreatic neuroendocrine tumors (GEP‐NETs) in the United States as well as the European studies demonstrate an increasing GEP‐NETs incidence. Most information on the epidemiology of neuroendocrine tumors comes from western countries. However, the epidemiological profile of GEP‐NETs in West China is still unclear. The aim of study was to reflect the regional features of GEP‐NETs in Chengdu city of West China based on data from a single institution. Methods: West China Hospital (WCH), the largest university hospital located in Chengdu (West China) with population of 14.04 million, has established a serial of databases in recent years. According to the data from Medical Records Section of WCH and Chengdu Health Bureau, the total patients per year in WCH covered about 25.6–28% patients of Chengdu city during the 5 years. Therefore, we have used GEP‐NETs diagnosed in WCH from 2009 to 2013 to reflect the regional epidemiological profile of GEP‐NETs. Results: GEP‐NETs proportion in WCH increased 1.6‐folds during past 5 years from 1.28/10 5 to 2.03/10 5, P < 0.05. The average duration of symptom before diagnosis was 16.8 months. About 46.6% (115/248) of GEP‐NETs were metastatic. Seventy‐seven percent (190/248) of patients were over 40 years. Proportions of GEP‐NETs from primary sites were rectum 30.6% (76/248), pancreas 23.4% (58/248), gastric 13.3% (33/248) and esophagus 11.3% (28/248). Proportions of insulinoma, vipoma and nonfunctional pancreatic neuroendocrine tumors (P‐NETs) were 43.1% (25/58), 1.7% (1/58) and 55.2% (32/58) separately in the P‐NETs. Conclusions: There is a distinct epidemiologic profile between West China and western countries based on a single institution data. The delayed diagnosis reflects inadequate disease awareness of GEP‐NETs and paucity of research funding.